Government bonds: European banks still display strong home bias; Requiring capital backing could worsen problem - Dorothea Schäfer; Michael Stöckel; Henriette Wese (DIW Weekly Report, 2020)
The European sovereign debt crisis illustrated how the stability of the entire financial system suffers when banks and sovereigns become too intertwined. However, there has been seemingly little success in reducing the bank-sovereign nexus in the decade since the crisis. As this Weekly Report shows, home bias remains strong and many European banks are still primarily purchasing domestic government bonds. One possible method of counteracting home bias would be to introduce a requirement for banks to back sovereign bonds on their balance sheets with their equity. So far, this has not been a requirement for banks, as government securities, which are inherently not free from risk, are considered risk-free from a regulatory perspective. However, as calculations in this report show, such a reform would entail a significant need for additional capital for many banks and could destabilize the euro area, especially as the home bias problem would become even more acute. Therefore, a future mandatory capital requirement for government bonds must be accompanied by additional measures, such as the introduction of a new, diversified type of government bond.
Keywords: G20; G28; G01; G38; G32; 330; Sovereign Exposure; Home Bias; Capital Requirement Regulation; Sovereign Bond Backed Securities